Monte Carlo modelling of Th-Pb fuel assembly with californium neutron source - Oettingen Mikołaj (Nukleonika, 2018)
This paper describes the methodology developed for the numerical reconstruction and modelling of the thorium-lead (Th-Pb) assembly available at the Department of Nuclear Energy, Faculty of Energy and Fuels, AGH University, Krakow, Poland. This numerical study is the first step towards integral irradiation experiments in the Th-Pb environment. The continuous-energy Monte Carlo burnup (MCB) code available on supercomputer Prometheus of ACK Cyfronet AGH was applied for numerical modelling. The assembly consists of a hexagonal array of ThO2 fuel rods and metallic Pb rods. The design allows for different arrangements of the rods for various types of irradiations and experimental measurements. The intensity of the fresh neutron source intended for integral experiments is about 108 n/s, which corresponds to the mass of about 43 μg 252Cf. The source was modelled in the form of Cf2O3-Pd cermet wire embedded in two stainless steel capsules.